A weak convergence approach to the theory of large deviations - Dupuis, Paul (Wiley series in probability and statistics)
This innovative text demonstrates how to employ the well-established linear techniques of weak convergence theory to prove large deviation results. Beginning with a step-by-step development of the approach, the book skillfully guides readers through models of increasing complexity covering a wide variety of random variable-level and process-level problems.